Perbandingan Kambing Azazel dalam Perjanjian Lama dan Witi Lera Wulang dalam Budaya Tenawahang - Yohanes Jemiandro Bala Kelen (Fakultas Teologi, Universitas Sanata Dharma, 2026)
This study aims to compare the Azazel goat in Leviticus 16 with the Witi Lera Wulang ritual in Tenawahang culture, East Flores, as ritual responses to collective purification and the restoration of cosmic harmony. Employing a qualitative approach with a descriptive-comparative design, the research analyzes primary data drawn from biblical texts and in-depth interviews with Tenawahang customary leaders, alongside secondary data from relevant scholarly publications. The findings reveal that both rituals share functional similarities in their use of a male goat as a medium for transferring collective burdens, the involvement of a ritual mediator, and the ultimate objective of restoring communal equilibrium. However, a fundamental divergence exists in their cosmological orientations: the Azazel rite emphasizes vertical reconciliation with Yahweh through the banishment of sin into the wilderness, symbolizing permanent separation from the divine presence, whereas Witi Lera Wulang prioritizes horizontal reconciliation that harmonizes relationships among humans, nature, and ancestors through a structured slaughtering sequence, communal feasting, and the distribution of blessings (kemie). Theologically and culturally, these results affirm that mechanisms of purification, reconciliation, and moral pedagogy constitute cross-culturally universal responses, while simultaneously underscoring the necessity of preserving the distinctive identity of each tradition within faith-culture dialogues. This study contributes to the advancement of contextual theology and ritual anthropology by offering a critical comparative framework for engaging indigenous knowledge systems and scriptural traditions.AbstrakPenelitian ini bertujuan membandingkan Kambing Azazel dalam Imamat 16 dengan witi lera wulang dalam budaya Tenawahang, Flores Timur, sebagai respons ritual terhadap pemurnian kolektif dan restorasi harmoni kosmis. Melalui pendekatan kualitatif dengan desain deskriptif-komparatif, penelitian ini menganalisis data primer dari teks Alkitab dan wawancara mendalam dengan tokoh adat Tenawahang, serta data sekunder dari jurnal ilmiah terkait. Hasil penelitian menunjukkan bahwa kedua ritual memiliki kesamaan fungsional dalam penggunaan kambing jantan sebagai medium transfer beban kolektif, peran mediator ritual, dan tujuan akhir berupa pemulihan keseimbangan komunitas. Namun, terdapat perbedaan mendasar dalam orientasi kosmologis; Azazel menekankan pendamaian vertikal dengan Yahweh melalui pengusiran dosa ke padang gurun sebagai simbol pemisahan permanen dari hadirat ilahi, sedangkan Witi Lera Wulang berfokus pada rekonsiliasi horizontal yang menyelaraskan hubungan manusia, alam, dan leluhur melalui siklus penyembelihan terstruktur, makan bersama, dan penyaluran berkat (kemie). Secara teologis-kultural, temuan ini mengonfirmasi bahwa mekanisme pemurnian, rekonsiliasi, dan pedagogi moral merupakan respons universal lintas budaya, sekaligus menegaskan pentingnya menjaga integritas identitas masing-masing tradisi dalam dialog iman-budaya. Studi ini berkontribusi pada pengembangan teologi kontekstual dan antropologi ritual dengan menawarkan kerangka komparatif yang kritis terhadap kearifan lokal dan tradisi kitab suci.